DAMPAK LITERASI KEUANGAN DAN GAYA HIDUP CASHLESS TERHADAP PERILAKU KONSUMTIF GENERASI Z DI KABUPATEN KLATEN (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2025)
This study aims to analyze the impact of financial literacy and a cashless lifestyle on the consumptive behavior of Generation Z in Klaten Regency. The research method employs a quantitative approach through a survey of 311 Generation Z respondents aged 18–25 years. Data were collected through questionnaires and analyzed using validity tests, reliability tests, and multiple linear regression. The results of the study show the following: Financial Literacy: The majority of respondents (63%) have a good level of financial literacy, especially in understanding budgeting and saving. However, understanding of debt-related risks remains low. Financial literacy has a significant negative effect on consumptive behavior, meaning that the higher the financial literacy, the lower the tendency toward consumptive habits. Cashless Lifestyle: About 59% of respondents actively use digital payment methods due to their convenience and efficiency, although there are concerns regarding security. A cashless lifestyle has a significant positive effect on consumptive behavior, indicating that the ease of digital transactions can encourage excessive spending. Consumptive Behavior: Around 47% of respondents exhibit moderate levels of consumptive behavior, with a tendency toward impulsive buying driven by discounts or promotions. The conclusion of this study highlights the importance of financial literacy in balancing a cashless lifestyle, enabling Generation Z to manage their finances wisely. Recommendations include enhancing financial education, improving understanding of debt risks, and fostering collaboration among stakeholders to support healthy financial management. This study contributes to understanding the dynamics of Generation Z's financial behavior in the digital era, offering practical recommendations to mitigate the negative impact of consumerism.
Keywords: Financial literacy; cashless lifestyle; consumptive behavior; Generation Z